Evaluation of In Vitro Antioxidant and Antidiabetic Activities of Aristolochia longa Extracts - El Omari, Nasreddine (Evid Based Complement Alternat Med, 2019)
Oxidative stress plays a major role in diabetic physiopathology; hence, the interest of using natural antioxidants as therapeutic tools exists. The aim of this study was the evaluation of in vitro antioxidant activity and inhibitory potential of organic extracts from Aristolochia longa roots against key enzymes linked to hyperglycemia. Antioxidant activity was performed using 2,2′-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) radicals and ferric reducing/antioxidant power (FRAP) methods. The α-Glucosidase and β-Galactosidase inhibitory activities were investigated using an in vitro model. Moreover, phytochemical analysis of tested extracts was carried out. The aqueous fraction of this herb exhibited the highest antioxidant activity for both DPPH and ABTS methods, IC(50)=125.40±2.40 μg/mL and IC(50)=65.23±2.49 μg/mL, respectively. However, the ethyl acetate fraction possessed the strongest inhibitory effect towards α-Glucosidase (IC(50)=1.112±0.026 mg/mL). Furthermore, the result showed high levels of phenolic content. The results showed that this plant could be a significant source of medically important natural compounds.